Assessing the Effectiveness of iOS Motion Cueing Technologies in Autonomous Vehicles - Kathir Velan Rethnam,; Abd Fathul Hakim Zulkifli, (Progress in Engineering Application and Technology, 2026)
This study investigates the effectiveness of iOS Motion Cueing technology in reducing motion sickness and improving passenger comfort in autonomous vehicles. Motion sickness is a common problem in autonomous driving, especially when passengers engage in non-driving activities such as reading or using mobile devices. In these situations, conflicts between visual input and vestibular sensations often cause discomfort, nausea, and reduced travel enjoyment, which can limit user acceptance of autonomous vehicle systems. Therefore, the main objective of this research is to evaluate whether the iOS Vehicle Motion Cues feature introduced in iOS 18 can reduce motion sickness symptoms and enhance the overall passenger experience. To achieve this objective, experimental testing was carried out using an instrumented vehicle driven along a real-road route within Universiti Tun Hussein Onn Malaysia. Participants were exposed to two experimental conditions, namely a baseline condition without motion cueing and a condition with iOS Motion Cueing enabled. Motion sickness responses were measured using Motion Sickness Dose Values, the Motion Sickness Susceptibility Questionnaire, and User Experience Questionnaire assessments, followed by statistical analysis to compare both conditions. The results show a clear reduction in motion sickness levels and noticeable improvements in comfort, stimulation, and dependability when motion cueing was applied. It is recommended that iOS Motion Cueing be further adopted and optimized as a simple and accessible solution to improve passenger comfort and acceptance in future autonomous vehicle applications.